Structural and normative conditions for interethnic friendships in multiethnic classrooms. (July 2015) - Schachner, Maja K.; Brenick, Alaina; Noack, Peter; van de Vijver, Fons J.R.; Heizmann, Boris
Abstract: Interethnic friendships between students are important for harmonious intercultural relations at school. Drawing on research on intergroup contact and cultural distance between immigrant and non-immigrant groups, we examined how structural and normative conditions in the classroom context are associated with friendships between early adolescents with and without an immigrant background in ethnically heterogeneous schools. The sample comprised 842 students ( M age  = 11.50 years, SD age  = .71; 53% male) attending multiethnic schools in Southwest Germany. Results revealed that perceived positive contact norms in class and perceived cultural distance predicted friendships between immigrant and non-immigrant students in both groups, even when the ethnic composition of the classroom was taken into account. The associations were largely the same for immigrants and non-immigrants. We conclude that interventions to foster interethnic friendships should aim to reduce perceptions of cultural distance and monitor and improve contact norms in intergroup settings.